2018
DOI: 10.1155/2018/8753463
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Potential and Clinical Implications of Giant Endometrial Polyps: A Case Report and Literature Review

Abstract: Endometrial polyps exceeding 4 centimeters in length are exceedingly rare and are termed “giant polyps.” We describe two patients that presented to our hospital with giant endometrial polyps. Clinical implications and oncologic potential of giant endometrial polyps are discussed. Risk factors of oncologic transformation include advanced age, menopausal status, obesity, diabetes, arterial hypertension, use of tamoxifen, and size greater than 1.0 centimeter. A literature review of all documented cases of giant e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Giant endometrial polyps, as seen in the present case study, are exceedingly rare variants of classical polyps. According to the pertinent world literature, there are <15 cases of giant endometrial polyps which have been reported so far[56891011121920212223] and a very small number have been documented from India. [2021] On reviewing the handful of cases mentioned till date, various clinicopathological features of this rare entity draws the attention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Giant endometrial polyps, as seen in the present case study, are exceedingly rare variants of classical polyps. According to the pertinent world literature, there are <15 cases of giant endometrial polyps which have been reported so far[56891011121920212223] and a very small number have been documented from India. [2021] On reviewing the handful of cases mentioned till date, various clinicopathological features of this rare entity draws the attention.…”
Section: Discussionmentioning
confidence: 99%
“…The most common presenting symptom is vaginal bleeding and only a few of them presented with an introital mass. [569212223] The polyp size varied from 4.5–12 cm in its greatest dimension. Maximum of the cases developed with the use of selective estrogen receptor modulators such as tamoxifen or raloxifene or a phytoestrogen (thyme).…”
Section: Discussionmentioning
confidence: 99%